A case of metastatic rectal adenocarcinoma diagnosed by thyroid cytology. Issue 8 (4th May 2020) - Sakaleshpura Mallikarjunappa, Subramanya; Valluru, Neelima; Park, Ji‐Weon; Gattuso, Paolo; Cheng, Lin
Abstract: Fine‐needle aspiration (FNA) cytology of the thyroid gland has been widely used for the evaluation of thyroid nodules. Most of the nodules are primary thyroid lesions. However, up to 4% of thyroid FNA may harbor a metastatic neoplasm. The metastases are most commonly from lung, kidney, breast, and skin. Metastatic colorectal cancers are also seen in thyroid but less common. Here we report the cytologic features, differential diagnosis and clinical implications of a metastatic rectal adenocarcinoma to the thyroid gland diagnosed by FNA.